THE INFLUENCE OF TIME BUDGET PRESSURE, AUDITOR EXPERIENCE, AND AUDITOR COMPETENCE ON AUDIT JUDGMENT - Fadhila Anditania Chairunnisa Hendar; Devianti Yuanita Harahap (Kajian Akuntansi, 2023)
This research aims to analyze the factors that can influence the audit judgments produced by auditors. These factors are time budget pressure, auditor experience, and auditor competence toward audit judgment. The operationalization of variables uses the independent variables of time budget pressure, auditor experience, and auditor competence. Furthermore, the dependent variable is audit judgment. In this research, primary data is used, and data collection instruments involve distributing questionnaires directly using paper media. The population for this study is active internal auditors registered in the Inspectorate of West Java Province, serving as team coordinators, senior team leaders, junior team leaders, senior team members, and junior team members. The entire population, which involves 40 auditors, is used as a sample using the Saturation Sampling technique, and the data analysis technique employed is Multiple Regression using Microsoft Excel STAT97 and Statistical Program from Society Science (SPSS) 23. The research findings indicate that, partially, time and budget pressure do not significantly affect audit judgment due to the obtained results being somewhat insignificant. However, both auditor experience and auditor competence significantly influence audit judgment. Keywords: Auditor Competence, Auditor Experience, Audit Judgmen,  Time Budget Pressure.